The role of rotational thromboelastometry in understanding the coagulation problems in COVID-19 associated critical illness - Duric, Natalie; Szakmany, Tamas (Anestezjologia Intensywna Terapia, 2021)
In critically ill patients with COVID-19, concomitant abnormalities of coagulation have been seen with an unusually high incidence, often despite seemingly appropriate prophylactic anti-coagulation. It appears that standard coagulation tests are limited in their ability to accurately reflect the severity of the prothrombotic phenotype observed in severe COVID-19 infections. In this narrative review we consider the role of a global haemostatic assay, rotational thromboelastometry (ROTEM), as a near bedside test allowing a more comprehensive assessment of haemostatic function in the context of COVID-19 infection. A comprehensive literature search was conducted on PubMed using the keywords “COVID-19” OR “SARS-CoV-2” AND “Rotational thromboelastometry”. Sixteen original articles were included for analysis and two existing literature reviews were considered. Whilst not the perfect substitute for in vivo coagulation, studies utilising rotational thromboelastometry assays in COVID-19 patients have demonstrated increased maximum clot firmness (consistent with hypercoagulability) and reduced maximum lysis (consistent with “fibrinolytic shutdown”). There is a possible association with disease severity and degree of hypercoagulability and hypofibrinolysis as a possible tool for risk stratification and the potential modulation of fibrinogen-dependent maximum clot firmness with enhanced anticoagulation strategies. Precisely how these coagulation abnormalities can be modified by optimum, individualised medical interventions to improve clinical outcomes, however, remains unclear.